An initial melanoma diagnosis may increase the subsequent risk of prostate cancer: Results from the New South Wales Cancer Registry - D. Cole-Clark; V. Nair-Shalliker; A. Bang; K. Rasiah; V. Chalasani; D. P. Smith (Scientific Reports, 2018)
Abstract Emerging evidence suggests that a diagnosis of cutaneous melanoma (CM) may be associated with prostate cancer (PC) incidence. We examined if the incidence of CM was associated with an increased subsequent risk of PC. We used data from the New South Wales Cancer Registry for all CM and PC cases diagnosed between January 1972 and December 2008. We calculated the age standardized incidence ratio (SIR) and 95% confidence intervals (95% CI) for PC incidence following a CM diagnosis, applying age- and calendar- specific rates to the appropriate person years at risk. We determined rate ratio (RR) and 95% CI of PC incidence according to specified socio-demographic categories and disease related characteristics, using a negative binomial model. There were 143,594 men diagnosed with PC or CM in the study period and of these 101,198 and 42,396 were diagnosed with PC and CM, respectively, as first primary cancers. Risk of PC incidence increased following CM diagnosis (n = 2,114; SIR = 1.25; 95% CI:1.20.8-1.31: p < 0.0001), with the increased risk apparent in men diagnosed with localised CM (n = 1,862;SIR = 1.26; 95% CI:1.20–1.32). CM diagnosis increased the subsequent risk of PC incidence. This raises the potential for future PC risk to be discussed with newly diagnosed males with CM.